Potensi Lactobacillus acidophilus dan Lactobacillus fermentum dari Saluran Pencernaan Ayam Buras Asal Lahan Gambut sebagai Sumber Probiotik - Manin, Fahmida (Fakultas Peternakan Universitas Jambi, 2010)
Probiotics are cultures of microorganisms included in the diets of cattle through mixing to ensure the availability of a population of organisms in the gut. The culture contains a specific bacterium, resistant in dry situations. Probiotics may contain one or more strains of microorganisms in the form of powder, tablets, granules or paste and can be given to livestock is directly through the mouth or mixed with water and feed. Probiotic products in general form of Lactic Acid Bacteria (LAB), and some of the genus Bacillus, but not all types of Lactic Acid Bacteria and Bacillus included in probiotic bacteria. Lactobacillus casei and Lactobacillus acidophilus reported to act as probiotics and to increase body weight in chickens. Similarly, Bacillus circulans and Bacillus Sp isolated from the digestive tract Kerinci local ducks can be used as a source of probiotics on chickens and ducks and effective for use as a substitute for antibiotics. This study aimed to determine the type and distribution of the dominant microbes in each segment of the digestive tract of chickens reared in peatlands, through isolation technique, identification and selection, and testing probiotic properties, including resistance to acid, resistance to bile salts and koagregasi test between microbes. Results Identification of the chicken digestive tract bacteria dipe; ihara in peatlands obtained Lactobacillus acidophilus and Lactobacillus fermentum. The test results obtained on the nature of the two types of probiotic bacteria were resistant to a pH ranging from pH 2.0 to pH 4, for 14 hours of incubation, that was resistant to bile salts up to 14 hours of incubation and hade a positive coaguration. In conclusion, probiotics production is expected to be applied to poultry, especially chickens.